The Increasing Students' Problem-Solving Abilities and Social Attitudes Using the Reciprocal Learning Model - Pangaribuan, Lena Rosdiana; Hasratuddin, Hasratuddin; Sinaga, Bornok (International Journal of Trends in Mathematics Education Research, 2024)
This research is a Classroom Action Research carried out in the Husni Thamrin school field with research subjects XI-IPA grade students the object of research is the application of models of reciprocal learning to increase mathematical problem solving and social attitude of students. This research consists of 2 cycles, each consisting of 2 meetings. The analysis data on cycle I indicated that (1) the average test scores for problem solving are 68,0 or 73% of the number of students who take the test can solve problems fairly minimal category and 27% had levels below the category of problem solving ability sufficient, (2) The value of obtaining students’ social attitudes is 2,0 including the bad category(3) current activity levels of students do not meet the ideal percentage of time specified, (4) there are 93,4% of total students taking learning to respond positively to the components and learning activities. In the second cycle, the results obtained : (1) the average test scores for problem solving abilities were 73,0 or 86,6% of the number of students taking the test can solve problems fairly minimal category and 13,4% had levels below the category of problem solving ability sufficient, (2) The value of obtaining students social attitudes is 3,50 including the excellent category, (3) current activity levels of students who meet the ideal percentage of the time, (4) there are 96,67% of the students gave a positive response to the components of learning activities. Based on the results of cycles I and II can be concluded that the implementation of reciprocal learning models can increase the problem-solving ability and social attitude of students.